2019
DOI: 10.2196/12245
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing User Engagement of Health Information Disseminated by Chinese Provincial Centers for Disease Control and Prevention on WeChat: Observational Study

Abstract: Background Social media is currently becoming a new channel for information acquisition and exchange. In China, with the growing popularity of WeChat and WeChat official accounts (WOAs), health promotion agencies have an opportunity to use them for successful information distribution and diffusion online. Objective We aimed to identify features of articles pushed by WOAs of Chinese provincial Centers for Disease Control and Prevention (CDC) that are associated with user… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 33 publications
3
20
0
Order By: Relevance
“…The median of the top three post views was chronic disease, nutrition and food-borne disease, and infectious disease, which indicated that these topics were more appealing to readers. This finding was almost the same as the prior study, which revealed that articles about infectious disease, food safety and nutrition, vaccination, and health life style were inclined to get more post views ( 28 ). It hinted that these kinds of issues should be strengthened in the OWA health information in future.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The median of the top three post views was chronic disease, nutrition and food-borne disease, and infectious disease, which indicated that these topics were more appealing to readers. This finding was almost the same as the prior study, which revealed that articles about infectious disease, food safety and nutrition, vaccination, and health life style were inclined to get more post views ( 28 ). It hinted that these kinds of issues should be strengthened in the OWA health information in future.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, the current results revealed that popular science articles were also popular with users, such as an article entitled “Running hot spots.” Our study showed that people liked to share posts with hot spots to their moments and friends, however it did not result in or contribute to higher amounts of post views and adds to favorites. A previous study demonstrated that articles with just hot spots were less likely to obtain high-level reading and liking than those with none ( 28 ). In other words, it implied that posts with hot spots should still be combined with high quality content ( 31 ), headlines, and other marketing elements ( 28 ) to achieve a better propagation effect.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we described a novel smartphone-based community approach for rehabilitation guidance and medical support in postoperative patients. This nonrandomized study showed that a social media-enhanced educational community is an effective Social media can influence lifestyle, including health behavior [23], especially for large groups of people [24]. In our study, 2292 out of 3428 (66.86%) patients who underwent joint replacement surgery were willing to participate in the WeChat-based community to evaluate the quality and the effect of postoperative care via the internet.…”
Section: Principal Findingsmentioning
confidence: 83%
“…Postgraduate students had a slightly higher supportive attitude about the NPI strategy than that of undergraduate students. Studies on Middle East respiratory syndrome (MERS)-related knowledge, preventive behaviors, and risk perception among nursing students during the MERS outbreak showed that senior nursing students and female students had a supportive attitude and practice of measures to control MERS [ 20 – 22 ]. These studies suggest that intelligence has a positive effect on the attitude towards a health strategy.…”
Section: Discussionmentioning
confidence: 99%